A Fiscal Stimulus and Jobless Recovery - Cantore, Cristiano; Levine, Paul.; Melina, Giovanni (Washington, D.C. : International Monetary Fund, 2013)
We analyse the effects of a government spending expansion in a DSGE model with Mortensen-Pissarides labour market frictions, deep habits in private and public consumption, investment adjustment costs, a constant-elasticity-of-substitution (CES) production function, and adjustments in employment both at the intensive as well as the extensive margin. The combination of deep habits and CES technology is crucial. The presence of deep habits magnifies the responses of macroeconomic variables to a fiscal stimulus, while an elasticity of substitution between capital and labour in the range of available estimates allows the model to produce a scenario compatible with the observed jobless recovery.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet